Respuestas

2013-05-03T04:26:44+02:00
2013-05-03T06:45:24+02:00

- (sec x + tan x)(1 - sen x) = cos x

(   1      +   sen x )(1 - sen x)  = cos x

  cos x       cos x

 

(   1      +   sen x )(1 - sen x)  = cos x

          cos x

 

(   12     -   (sen x)2 ) = cos x

          cos x

 

(cos x )2  =  cos x

  cos x

 

  cos x = cos x

 

- (f + g)(2)

f(x) + g(x) = 3x -2 + x3 = x3 + 3x - 2

(f + g)(2) = (2)3 + 3(2) - 2 = 8 + 6 - 2 = 12

 

- (f - g)(2)

f(x) - g(x) = 3x -2 - x3 = - x3 + 3x - 2

(f - g)(2) = - (2)3 + 3(2) - 2 = - 8 + 6 - 2 = - 4

 

- (f . g)(2)

f(x) . g(x) = (3x -2) . (x3) = 3x4 - 2x3

(f - g)(2) = 3(2)4 - 2(2)3 = 3(16) - 2(8) = 48 - 16 = 32

 

- (f / g)(2)

f(x) / g(x) = (3x -2) / (x3) = (3/x2) - (2/x3)

(f / g)(2) = (3/(2)2) - (2/(2)3) = (3/4) - (2/8) = (3/4) - (1/4) = (3-1)/4 = 2/4 = 1/2